If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6k + -5 = -10 Reorder the terms: 1 + -5 + -6k = -10 Combine like terms: 1 + -5 = -4 -4 + -6k = -10 Solving -4 + -6k = -10 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -6k = -10 + 4 Combine like terms: -4 + 4 = 0 0 + -6k = -10 + 4 -6k = -10 + 4 Combine like terms: -10 + 4 = -6 -6k = -6 Divide each side by '-6'. k = 1 Simplifying k = 1
| 4/7*21/32 | | -(x+5)=-7-x | | 4z/10-6=-5 | | 10n=99 | | 157+78+x=180 | | 4+kx=4x^2 | | 11.6=v+4.4 | | .2f+.6(f+20)=-.8+.4f | | 12/r=3 | | 2=-1*-3+b | | -8v+36=-6(6v-6) | | 6k+8-k=-7 | | 120+78+15+x=180 | | f(x)=15x^2-33x-36 | | x=65/11 | | 4=2*-9+b | | 4=2*-9 | | 25x^2+20x=15 | | Fancy+1=0 | | 1/8*21/32 | | x=48/7 | | 121=-x-7(7x-3) | | 6(1-4x)-3x=-26+5x | | 5c+6=51 | | 0.25d-10=5 | | 52-3c=-15 | | -3=6*4+b | | -3.8=m-4.2 | | 3c-5=32 | | -12+8yi=3x-i | | x=36/7 | | 0.25d-10=-5 |